Analisis Penentuan Harga Jual Untuk Barang Preloved (Studi Kasus Pada Bisnis Barang Preloved @Bekasberkualitaz) - Dewi, Diah Chandra; Atmadja, Anantawikrama Tungga (Universitas Pendidikan Ganesha, 2020)
Determination of the sellinggpriceeis something that needs to be considered considering the selling price will affect the sustainability of the business. It is undeniable thattthe selling price can increaseltheeamount received. This study uses qualitative methods, with observations,iinterviews, and observations.tTheaanalysis techniqueeissdoneebyyskipping dataareduction, then presenting data and drawing conclusions. The results of this study indicate that research on consumptive, demand and supply, market and e-commerce which attracts business debates that have been carried out before, in addition to determining the selling price carried out by @bekasberkualitaz with the price mark up method to obtain the method using the cost plus price method.Â